'I Do Not Want Her to be Doing Anything Stressful': Men's Involvement in Domestic Work During Pregnancy in Ghana. (October 2022) - Ampim, Gloria Abena; Haukanes, Haldis; Blystad, Astrid; Kpoor, Albert
Drawing on qualitative research from rural and urban areas, this article contributes to evolving social research in Ghana on possible changes in the gendered distribution of domestic labour. Formulated within debates on 'doing gender' and 'undoing gender', this study examines the extent to which acts of gender transgression may potentially occur during peak reproductive periods in the lives of Ghanaian couples. The findings of the study indicate that the participants reiterated normative gendered definitions of men as primary providers and women as primary domestic caretakers. Nonetheless, it was noted that during their partner's pregnancy, men in both urban and rural areas were willing to modify their daily schedule to incorporate more housework. Simultaneously, men's involvement in all or most of the household chores was perceived as potentially dangerous to the gendered balance of labour in the family and could, according to the participants, stimulate laziness among female partners. Despite the apparent resistance to male performance of domestic chores, the article argues that men's willingness to do housework during their partner's pregnancy may be an early indicator of slow but steady transformations in gender relations in Ghana.